ปัญหาการจัดการท้องถิ่นขององค์กรปกครองส่วนท้องถิ่นในพื้นที่เมืองการค้าชายแดน: กรณีศึกษาเทศบาลตาบลท่าสายลวด และเทศบาลนครแม่สอด อาเภอแม่สอด จังหวัดตาก - อัคฮาด, นพพล (Thai Interdisciplinary and Sustainability Review, 2019)
The purpose of this research was to study Local government with border area management that how local government has any abilities to administrate itself and how characteristic local government which located in border has abilities to handle problems that isdifferent from general local government. The result of the study Local government with border management reveals that localgovernment which located in border confronts with many problems which are arised from 2 factors. The first factor is neighbor such as migrant labor, and the second factor is internal area such as road map, garbage, cleanness and flood etc. Therefore, these problems directly impact on people in the area that are different from general local government which confronts only internal problems and Local government organization cannot efficiently handle many problems in the area due to, firstly, decentralization only potentiates to mayor but budget, subvention, and subsidy are not sufficient to maintain local people. In addition, the lack of budget which leads to insufficient staff to handle problems. Secondly, Local government organization has not had obvious extent because of functional overlapping with other government agencies. Eventually, Municipal district organization cannot achieve solving the problems as above.